(untitled) - Riley, Mike (New York, 2005)
Construction Technology 3: The Technology of Refurbishment and Maintenance is specifically designed to be a genuine learning text that will support your study of construction technology and management courses in refurbishment and maintenance. Uniquely, it covers the technology of refurbishment in both housing and large-span, multi-storey commercial and industrial buildings
Keywords: Building